厦语电影与华语语系的 “方言问题“ = Amoy-dialect cinema and the "Problem of Chinese Dialects" in Sinophone studies - 杨明慧 Yeo, Min Hui (2016)
厦语电影是个鲜少人记得的华语电影片种。一方面，这是因为厦语电影于上世纪四十年代末诞生，六十年代初便已销声匿迹，短短二十年间，足迹匆匆，印记易淡。另一方面，厦语影业虽然横跨香港、台湾、菲律宾和新马，但这跨国界的片种如今却难以被归纳进任何一个国家的民族电影历史里，导致这段历史长久以来未能受到学术界的重视。 近十几年来，随着华语电影研究范式的拓展，已有学者开始着手建构厦语电影的历史。然而，在目前的厦语电影历史叙事当中，仍缺乏新马面向和关于这文化产品本身的演变的讨论。除此之外，目前关于厦语电影的学术讨论也仍甚少。若从文化研究的角度来看，厦语电影这独特的方言片种其实可以成为一个有趣的研究个案，有助于探索目前试图干预社会政治现实的华语语系研究尚未充分开拓的论述层面，即汉语方言与祖籍地，以至于中国境外华人社群与祖籍地之间的关系。作为一个全然在祖籍地以外萌芽发展的方言文化生产，厦语电影与祖籍地之间，存在着什么样的关系，而对于生活在祖籍地以外的厦语电影观众而言，这方言文化生产又具有什么样的意义？探讨这些问题不仅有助于进一步加深厦语电影历史的建构，同时可以拓展华语语系的话语建构，帮助深化华语语系的立论基础。正是以补充上述电影历史和华语语系研究中的不足为动机，本论文将运 用来自新马的一手材料，并以主导音乐类型的角度，以及 Deleuze 与 Guattari 提出的，关于“畛域”（territory）的概念，来阐述和论析厦语电影这方言文化生产在新马的发展，以及其与祖籍地之间，不断变动着的关系，由此希望加深厦语电影的历史建构，同时加强华语语系的话语建构，深化华语语系研究的立 论基础。 The short-lived nature of the genre itself, coupled with the paradigmatic dominance of “National Cinema” in Cinema Studies have long stunted the study of Amoy-dialect cinema – an industry with a unique transnational production and distribution network connecting Hong Kong, Taiwan, the Philippines, Singapore and Malaya from the late 1940s to the early 1960s. It is only in recent years that Amoy-dialect cinema history finally received some academic attention following the advent of alternative paradigmatic possibilities. However, much still remains to be done in documenting the history of this unique cinematic genre, and it is to this ongoing work that this paper wishes to contribute to. Besides Cinema Studies, the field of Sinophone Studies has also been actively reinventing itself in a bid to further its strength and potential for reform. Over the past decade, Sinophone Studies constantly revised its definitions and parameters in order to better tackle the complexity of identity and cultural politics inherent in the use of Sinitic languages all over the world. However, as a relatively new discourse, there is still much room for improvement in its conceptualization. This paper wishes to address one particular problem and area that has yet to be satisfactorily theorized and discussed in Sinophone Studies: the relationship between Chinese dialects and their respective ancestral home villages. Recognizing that the study of Amoy-dialect cinema history can potentially help to solve this “problem of Chinese dialects” in Sinophone Studies while at the same time contribute to the construction of a more inclusive cinema history, this paper aims to pave two interrelated tracks of discussion using Amoy-dialect cinema as its object of study: Using first-hand materials that had once circulated within Singapore and Malaya, this paper seeks to document the transformation of Amoy-dialect cinema, with a focus on the development of music genre in these films. Simultaneously, using Deleuze and Guattari’s concept of “territory”, this paper also attempts to analyze the changing relationship between this dialect cultural production and its ancestral home village, as well as what it could have meant, for Amoy-dialect communities living outside of their ancestral home village, to consume this cultural product at each of its different stages of development.